The Significance of Technology in Digitalising Malaysia Industries - Choon Sen Seah; Yin Xia Loh; Aman Lew Ka Lock Bin Lew Kat Keong; Min Xuan Chin; Gabriel Chuen Lio; Mei Kay Lee; Li Bin Lim; Shin Jer Wong (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Digitalisation enables a business to produce, adapt and innovate digital technologies and services to enhance wealth creation, productivity, and quality of life. Various latest technology such as Artificial Intelligence (AI), Machine Learning (ML), Internet of Things (IoT), collaborative robots (cobots) is discussed. During the era of the Industrial Revolution 4.0 (IR 4.0), many corporates in Malaysia started to implement the technologies. BMW Malaysia has implemented automated image recognition. UOB Malaysia has launched Mighty Insights. Ernst & Young using Robotic Process Automation in their business operation. Symprio is using a chatbot design agency to assists in organizations design. Even though many corporates in Malaysia are accepting these new technologies but these new technologies had become the barriers for some small and medium enterprise in Malaysia to move forwards. Challenges to implementing technologies are identified and discussed in this study.